Calculation of intense rain by the method of isozonas for cities the state of Paraíba - Santos, Robson Arruda dos; Lucena, Pedro Gomes de; Carvalho, Rafaela da Silva (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This work presents the application of obtaining intense rains, used in hydraulic structures, through the method of Isozonas. This method is based on the observation made by the Engineer José Jaime Torrico. The objective is to calculate the intense rains through the software "ISO- P" for major cities of the state of Paraíba, proposing values that can be adopted in projects in these cities as well as neighboring cities. The calculation of intense rains was performed using the software " ISO - P”, tool easy to apply the method of Isozonas, with the data the historical series from the ANA website. It presents tabulated data of rainfall intensity for the cities of Cajazeiras, Sousa, Patos, Monteiro, João Pessoa and Campina Grande. Comparing the values of NBR 10844, 1989, some data show values variation, we can justify with respect to the historical series, which in its update may have included some weather event that caused this change in the values of intense rain; and the duration of the rain, the method of isozonas considers a minimum duration of 6 min, different the duration considered by NBR 10844/89, which is 5 min.